Bare necessities? The utility of full skin examination in the COVID‐19 era. (18th March 2021) - O'Connor, C.; Gallagher, C.; O'Connell, M.; Bourke, J.; Murphy, M.; Bennett, M.
Summary: Full skin examination (FSE) may improve the detection of malignant melanoma (MM). The objective of this study was to assess the safety of targeted lesion examination (TLE) compared with FSE in our Pigmented Lesion Clinic (PLC). Patients attending the PLC were randomized in a 2 : 1 ratio to FSE (intervention) or TLE (standard care). Demographic details and risk factors were documented, and the time taken to perform FSE and TLE was noted. Of 763 participants, 520 were assigned to FSE and 243 were assigned to TLE. On average, FSE took 4.02 min and TLE took 30 s to perform. Of the 520 participants assigned to FSE, 37 (7.1%) had incidental findings, of whom 12 patients (2.3%) had additional lesions biopsied. No additional melanomas were detected that would have been missed by use of the standard protocol. This study suggests that in low‐risk patients referred to a PLC with a lesion of concern, the possibility of missing incidental cutaneous malignancies using lesion‐directed examination is low.